KARAKTERISASI PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS PADI AKIBAT PENGATURAN JARAK TANAM YANG BERBEDA DI LAHAN SAWAH IRIGASI - Turmuktini, Tien; Widodo, Wahyono; Kanta, Kanta (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
The use of supreme paddy varieties is one of the major technologies, which canincrease paddy productivity. With the availability of paddy varieties that has beenreleased by government, farmers are now able to select varieties that compatible to thelocation, high yield, and high selling value. Every paddy varieties require differentmanagement, in order to obtain optimal production is necessary to adjust the varietiesand cropping methods for a certain environment in obtaining the desired level of resultswith limited land area. The difference yield from each different spacing is not as much aseach different variety. Based on those things, the study was conducted in order todetermine the growth characterization and yield of several paddy varieties with differentspacing on irrigated soil. The research was conducted from April to August 2009, inKabupaten Karawang, using Split Plot Design with four replications. The main plot:plant spacing (20 cm x 20 cm and 27 cm x 27 cm), while the subplot: paddy varieties (4Hipa Ceva, Hipa 6 Jete, SL8 SHS and Ciherang). Research shows: no interactionbetween the spacing of rice varieties to growth characterization and paddy yield. Theresult of independent test shows that the different spacing has en effect on growthcharacterization and paddy yield. Spacing of 27 cm x 27 cm, showing the number oftillers per hill, percentage of filled grain per panicle, filled grain weight per hill and thehighest yield per plot 7.17 tonnes per hectare. Different paddy varieties influence growthcharacterization and paddy yield. SL8SHS and Ciherang varieties produce a low numberof tillers, but shows the highest percentage of filled grain per panicle, filled grain weightper hill and the highest yield per plot with results of each 7.47 and 7.37 tonnes perhectare.